Predominantly cytoplasmic localization in yeast ASR1, a non-receptor transcription factor from plants - Urtasun, Nicolás (2010)
The Asr gene family (named after abscisic acid, stress and ripening), currently classified as a novel group of the LEA superfamily, is exclusively present in the genomes of seed plants, except for the Brassicaceae family. It is associated with water-deficit stress and is involved in adaptation to dry climates. Motivated by separate reports depicting ASR proteins as either transcription factors or chaperones, we decided to determine the intracellular localization of ASR proteins. For that purpose, we employed an in vivo eukaryotic expression system, the heterologous model Saccharomyces cerevisiae, including wild type strains as well as mutants in which the variant ASR1 previously proved to be functionally protective against osmotic stress. Our methodology involved immunofluorescence-based confocal microscopy, without artificially altering the native structure of the protein under study. Results show that, in both normal and osmotic stress conditions, recombinant ASR1 turned out to localize mainly to the cytoplasm, irrespective of the genotype used, revealing a scattered distribution in the form of dots or granules. The results are discussed in terms of a plausible dual (cytoplasmic and nuclear) role of ASR proteins.